2021
DOI: 10.1021/acssynbio.0c00491
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Cell Biosensor for Point-of-Care Detection of Waterborne Bacterial Pathogens

Abstract: Water contamination by pathogenic bacteria is a major public health concern globally. Monitoring bacterial contamination in water is critically important to protect human health, but this remains a critical challenge. Engineered whole-cell biosensors created through synthetic biology hold great promise for rapid and cost-effective detection of waterborne pathogens. In this study, we created a novel whole-cell biosensor to detect water contamination by Pseudomonas aeruginosa and Burkholderia pseudomallei, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 79 publications
0
31
0
Order By: Relevance
“…In Table 2, the quorum-sensing molecules, bacterial species, the responding genetic systems, and the corresponding TF-based biosensors are summarized. Recently, many TF-biosensors have been developed for detecting pathogenic microorganisms by targeting quorum sensing (QS) molecules [76,87,88]. Quorum sensing is the ability to detect and respond to cell population density by gene regulation [89,90].…”
Section: Bacterial Cell-based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 2, the quorum-sensing molecules, bacterial species, the responding genetic systems, and the corresponding TF-based biosensors are summarized. Recently, many TF-biosensors have been developed for detecting pathogenic microorganisms by targeting quorum sensing (QS) molecules [76,87,88]. Quorum sensing is the ability to detect and respond to cell population density by gene regulation [89,90].…”
Section: Bacterial Cell-based Biosensorsmentioning
confidence: 99%
“…Recently, many TF-biosensors have been developed for detecting pathogenic microorganisms by targeting quorum sensing (QS) molecules [ 76 , 87 , 88 ]. Quorum sensing is the ability to detect and respond to cell population density by gene regulation [ 89 , 90 ].…”
Section: Tf-based Biosensors For Detecting Pathogensmentioning
confidence: 99%
“…Recently, Wu et al created a novel whole-cell biosensor to detect bacterial pathogens ( P. aeruginosa and Burkholderia pseudomallei ) by responding to the relevant QS signal molecules. Results showed that engineered whole-cell biosensors provide rapid and cost-effective detection of waterborne pathogens ( Wu et al, 2021 ).…”
Section: Microbial Control Systemsmentioning
confidence: 99%
“…Moreover, the ad hoc detection and monitoring of bacterial infections [21,22] can provide convenience for the patients and improved healthcare in hospitals. Testing food and water contamination is another area where biosensors excel in terms of cost effectiveness and as rapid assay tools [23][24][25]. In short, biosensors provide portability and the rapid, low-cost, and early diagnosis of pathologies such as cardiac or neurodegenerative diseases, infectious diseases, cancer, fatal viruses, bacterial infections, pregnancy tests, and more, anywhere and anytime.…”
Section: Introductionmentioning
confidence: 99%